Turn-Taking Between Provisioning Parents: Partitioning Alternation - Baldan, Davide; Hinde, Camilla A.; Lessells, Catherine M. (Frontiers in Ecology and Evolution, 2019)
How parents negotiate over parental care is a central issue in evolutionary biology because it affects the evolutionary outcome of sexual conflict. A recent theoretical model shows that ‘turn-taking’ in provisioning visits by the parents is an evolutionarily stable negotiation strategy, and empirical studies have shown that parental nest-visits do indeed alternate more than expected by chance. However, such alternation may also be generated by a refractory period, or by correlated temporal heterogeneity (CTH) in provisioning rates of the two parents driven by temporal environmental variation. Here we use a recently developed measure of alternation and a novel measure of CTH in the provisioning rates of pairs to clarify what can be concluded about the occurrence of turn-taking from the provisioning patterns of pairs. First, we show using a simulation model that turn-taking can, by itself, generate both a refractory period and CTH in provisioning rates. Second, we incorporate this insight into a conceptual framework that combines an existing randomization analysis with a novel analytical approach in which ‘pseudo-pairs’ are created by analytically pairing the provisioning sequence of a parent at one nest with the contemporaneous provisioning sequence of the other-sex parent at a nearby nest. This allows us to partition the alternation score into different components. This approach confirms that isolating a component of alternation that can be unequivocally attributed to turn-taking is probably impossible. However, the pseudo-pairs analysis does isolate a component that can be unequivocally attributed to general temporal environmental variation (environmental variation that causes CTH in provisioning rates across [as well as within] pairs). Third, we use these techniques to partition the alternation score of 17 pairs of great tits Parus major provisioning in the wild. Approximately 8% of the observed alternation score is due to the frequency distribution of the inter-visit intervals, 74% to nest-specific effects on the sequence of inter-visit intervals, and 18% to general effects on the sequence of inter-visit intervals. This last component can be unequivocally attributed to general temporal environmental variation, and is the first empirical demonstration of alternation by free-living provisioning parents being generated by temporal environmental variation.